THE ROLE OF ENZYMES IN IMPROVING SOIL FERTILITY - Tagayeva, Muhayo (Центр Научных Публикаций (buxdu.uz), 2023)
In the article, it is fully explained that the activity of catalase, protease, peroxidase enzymes in the soil under the influence of green microalgae can increase soil fertility in irrigated meadow alluvial soil.